2019
DOI: 10.1002/sctm.18-0287
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Patency of Small-Diameter Tissue-Engineered Vascular Grafts: A Meta-Analysis of Preclinical Trials

Abstract: Several patient groups undergoing small‐diameter (<6 mm) vessel bypass surgery have limited autologous vessels for use as grafts. Tissue‐engineered vascular grafts (TEVG) have been suggested as an alternative, but the ideal TEVG remains to be generated, and a systematic overview and meta‐analysis of clinically relevant studies is lacking. We systematically searched PubMed and Embase databases for (pre)clinical trials and identified three clinical and 68 preclinical trials ([>rabbit]; 873 TEVGs) meeting the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 102 publications
1
53
0
Order By: Relevance
“…The next step of the current study will be the development of a rapid and effective recellularization approach utilizing mostly the ECs. A recent metanalysis conducted by Skovrind et al [ 45 ], reported that there is no immediate benefit to the patency from recellularized vascular grafts with VSMCs (with or without ECs). For this purpose, our future studies will focus on the production of endothelialized TEVGs, and to assess their functionality as grafts by implantation to animal models.…”
Section: Discussionmentioning
confidence: 99%
“…The next step of the current study will be the development of a rapid and effective recellularization approach utilizing mostly the ECs. A recent metanalysis conducted by Skovrind et al [ 45 ], reported that there is no immediate benefit to the patency from recellularized vascular grafts with VSMCs (with or without ECs). For this purpose, our future studies will focus on the production of endothelialized TEVGs, and to assess their functionality as grafts by implantation to animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical evaluation in small-or large-animal models may effectively predict the success of vascular grafts if tested in clinical trials, and approaches to evaluating the patency of TEVGs with long-term follow-up are well established. 16,38,105,106 Moreover, a nanotechnology-based non-invasive strategy has recently been developed for real-time serial monitoring of cell-based TEVGs in vivo. 87 Beyond molecular imaging data, in vivo parameters, such as compliance and pulsatile flow, are critical criteria that can be effectively applied to determine the success of tissue-engineered blood vessels in clinical trials.…”
Section: Preclinical Evaluation Of Engineered Blood Vesselsmentioning
confidence: 99%
“…14,15 Given the shortage of available vascular bypass conduits, tissue engineering technology combines cells, tissue scaffold and engineering to generate vascular graft, and is thus a potential solution for vascular surgery. 16 A tissue-engineered vascular graft (TEVG) generated in vitro does not require invasive surgery to harvest vascular tissues from patients. Development of functional TEVGs is essential for other applications of tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, functionalization of TEVGs with biological signals such as the angiogenic cytokine VEGF have been shown to trigger in situ tissue endothelial regeneration (Koobatian et al, 2016). Although advances in traditional translational approaches for cardiac anomalies have paved the way for regenerative medicine, these TEVGs still suffer from a number of common issues including insufficient patency, integration, hemodynamics, immune-compatibility with the graft cell source and mechanical strength, as outlined by others (Pashneh-Tala et al, 2016;Matsuzaki et al, 2019;Skovrind et al, 2019).…”
Section: Regenerative Medicinementioning
confidence: 99%